Method for calculating pumping characteristic of high-vacuum system with turbomolecular vacuum pump - N. Yu. Fil’kin; V. L. Yusha; A. A. Kapelyukhovskaya (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The article is devoted to the problem of increasing the gas dynamic efficiency of gas filters with a short diffuser when working in a swirling flow, the perturbation of which is caused by the presence of local resistance. To increase the gas dynamic efficiency, installation of a concentric guides in the flowing part of the short diffuser is suggested, as well as an engineering technique for calculating such guides. Numerical and experimental studies of the gas filter are carried out when working in a stream swirling by means of a tee, with the installation and without the installation of a concentric guides in a flowing part, comparative results of the studies are presented. Based on the results of the research, the efficiency of concentric guides in the conditions of a swirling flow is confirmed, and the gas-dynamic efficiency of the gas filter is improved in comparison with the version without the installation of guides in the flowing part of the short diffuser